Principles of SARS-CoV-2 glycosylation. (August 2022) - Chawla, Himanshi; Fadda, Elisa; Crispin, Max
Abstract: The structure and post-translational processing of the SARS-CoV-2 spike glycoprotein (S) is intimately associated with the function of the virus and of sterilising vaccines. The surface of the S protein is extensively modified by glycans, and their biosynthesis is driven by both the wider cellular context, and importantly, the underlining protein structure and local glycan density. Comparison of virally derived S protein with both recombinantly derived and adenovirally induced proteins, reveal hotspots of protein-directed glycosylation that drive conserved glycosylation motifs. Molecular dynamics simulations revealed that, while the S surface is extensively shielded by N-glycans, it presents regions vulnerable to neutralising antibodies. Furthermore, glycans have been shown to influence the accessibility of the receptor binding domain and the binding to the cellular receptor. The emerging picture is one of unifying, principles of S protein glycosylation and an intimate role of glycosylation in immunogen structure and efficacy. Graphical abstract: Image 1 Highlights: The glycosylation of SARS-CoV-2 viral spike resembles recombinant spike protein. The entry of SARS-CoV-2 viral spike is mediated by S-ACE2 interaction. Glycans help in stabilising RBD dynamics which facilitates receptor recognition. Glycan maturation on S protein can be influenced by the local protein architecture. Antibodies can exploit breaches within the glycan shield of SARS-CoV-2.